Directive Speech Act Translation Analysis in “The Lion King” Movie - Candra Lesmana; Muhammad Aprianto Budie Nugroho; Wulan Rahmatunisa; Arbain Arbain (Borneo Educational Journal (Borju), 2022)
Abstract: The purpose of this study is to find out the equivalence of directive speech act and its translation techniques in The Lion King movie. The study used the script of The Lion King movie, and its two kinds of subtitles, namely the professional translator version and the fansub version. A qualitative case study is used as research design while documentation is considered as the tool. The results found 6 types of directive speech acts among 143 directive speech acts. All of directive speech act in the movie “The Lion King” are translated equally by professional and fansub translators. There are also 272 translation grouping techniques in this study: 1) 115 (42,3%) total of single group techniques in both professional and fansub translation. 2) 114 (41,9%) total of duplet group technique in both professional and fansub translation. 3) 31 (11,4%) total of triplet group techniques in both professional and fansub translation. 4) 12 (4,4%) total of quadruplet group techniques in both professional and fansub translation. Literal translation is the most found type of translation technique, intended to translate simple texts and dialogues. Therefore, an easy language requires an equally comprehensible translation as well. Keywords: Translation Analysis, Directive Speech Act, Professional Translator, Fansubtitle